Isokinetic evaluation of the ankle plantar and dorsiflexion strength to determine the dominant limb in basketball players - Theoharopoulos, A.; Tsitskaris, G. (2000)
The purpose of this study was to demonstrate limb dominance normative strength values (peak torque, relative peak torque, work and relative work) for the plantar and dorsiflexion muscles in professional basketball players, using the Cybex 1200 isokinetic dynamometer. Paired t-tests showed no significant differences between the two limbs, except for peak torque and relative peak torque during plantar flexion at 60^{°}/s (p<0.05). The ratio plantar/dorsiflexion was also analyzed, with no significant difference between the two limbs. The results of this research study provide very useful information about the level of strength in this particular area, and are useful for prescribing proper rehabilitation programs for injured basketball players. Isokinetics and Exercise Science, Issue: Volume 8, Number 4/2000, Pages: 181 - 186